THU0730-HPR A systematic review of online interventions for addressing psychological distress in rheumatoid arthritis and other long-term conditions. (12th June 2018) - Fishpool, K.; Jones, B.; Hewlett, S.; Ndosi, M.
Abstract : Background: Psychological distress in rheumatoid arthritis (RA) is associated with severity of disease activity and poor treatment outcomes. Online interventions have the potential to reach large numbers of patients. Objectives: The aims of this study were to identify online interventions for psychological distress and determine their effectiveness in RA and other long-term conditions. Methods: The following databases were searched: MEDLINE, EMBASE, CINAHL and PsychINFO Jan 2007-Jul 2017). Inclusion criteria were randomised controlled trials (RCTs) of effectiveness of interventions to address psychological distress in adults. Titles and abstracts were screened independently by 2 reviewers. Methodological quality was assessed by 3 reviewers using Cochrane's Risk of Bias tool. Data were extracted independently by 4 reviewers. Meta-analysis was not possible due to clinical heterogeneity of the included studies. Effectiveness of interventions is reported with effect sizes based on between-group differences in the primary outcomes at the end of each study. Results: The review included 11 RCTs in the following conditions: arthritis, 2 multiple sclerosis, 2 diabetes 6 and irritable bowel syndrome. 1 The quality of most RCTs was poor due to attrition, selective reporting and limited follow-up. Eight disease-specific and 3 generic interventions were identified. Cognitive behavioural therapy was the most common intervention type. All interventions were online but support delivery and outcome measures varied significantly, Nine of the 11 interventions were shown to be effective, including 2 for RA. Most interventions were not available outside of the trial. Conclusions: The findings are inconclusive due to the overall bias of the included studies and insufficient evidence in RA. More good quality RCTs are required to determine effectiveness of online interventions in RA. Acknowledgements: This study was funded by Arthritis Research UK. Disclosure of Interest: None declared